Incorporating measures of sleep quality into cancer studies. - Redeker, Nancy S; Pigeon, Wilfred R; Boudreau, Eilis A (Supportive Care in Cancer, 2015)
Introduction/background: Sleep disturbance may influence the development of cancer and responses to treatment. It is also closely tied to recovery and quality of life in cancer patients, survivors, and caregivers, and recent studies have begun to show beneficial effects of sleep-promoting interventions. Despite the importance of sleep to cancer and its treatment and the availability of numerous tools for measuring sleep quality and quantity, sleep measurements are underutilized in cancer studies.Methods: This review, written for cancer researchers interested in incorporating sleep measures into their studies, is designed to raise awareness about the importance of sleep and suggests strategies for including sleep evaluation in cancer studies.Conclusions: Inclusion of readily available sleep measures may ultimately improve cancer care by facilitating studies that lead to a greater understanding of how sleep and sleep disturbance influence all aspects of cancer care and the patient experience.